ANALYSIS ON RESPONSE OF TOWER CRANE STRUCTURES UNDER RANDOM EARTHQUAKE EXCITATIONS - WANG PingPing; YU LanFeng; HAN Wei; TANG Hui; YAN Fei; ZHAO DengShan (Jixie qiangdu)
Based on the theory of random vibration,the dynamic response on tower crane under random seismic excitation was investigated. The input of earthquake ground motion is indicated by Duxiuli-Chenhouqun power spectral. The random seismic responses of structural ’s force and displacement were researched under five different earthquake model input with uniform earthquake excitations method. The analysis reveals that the force of tower crane increase significantly under vertical seismic excitation than X-direction,Z-direction excitation have the greatest influence in tower body bending moment; the primary reason of tower arm fracture is vertical seismic action,too large seismic wave cause tower body capsized easily.